Dampak Penerapan Digital Media Center pada Efektivitas Corporate Communication PT United Tractors Pandu Engineering - Fauziah, Raden Gladis Muthia; Santoso, Hudi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The advancement of digital technology requires companies to manage corporate communication more effectively, efficiently, and data-driven. This study aims to analyze the impact of implementing the Digital Media Center (DMC) on the effectiveness of corporate communication at PT United Tractors Pandu Engineering (UTPE). The research was conducted from July to September 2023, involving five key informants from the Corporate Communication Division. A qualitative approach was employed through observation, in-depth interviews, and literature review, with thematic analysis used to identify patterns and meanings from the interview data. The findings show that DMC enhances work efficiency, data accuracy, and coordination among Internal, External, and Brand Communication sub-divisions through an integrated digital system. DMC also supports data-driven strategic decision-making through analytic dashboards and automated reporting. The success of DMC implementation is influenced by management support, data readiness, internal technical capability, and cross-divisional collaboration. The novelty of this study lies in developing DMC as the first integrated corporate communication system at UTPE, adopting the AMEC framework for measuring communication effectiveness. Theoretically, this research enriches the study of organizational digital communication, while practically, it provides a model for implementing data-driven communication systems in companies undergoing digital transformation. These findings extend the application of digital organizational communication theory by demonstrating how integrated data-based communication systems can strengthen evidence-based decision-making processes in Indonesian manufacturing companies.
Keywords: Digital Media Center; Corporate Communication; Digital Transformation; Data Integration; PT United Tractors Pandu Engineering